Proposal for a Stratification Tool for Emergency Department Diabetic Patients with Uncomplicated Acute Hyperglycemia - Luís Alberto Corona Martínez; Laydami Rodríguez Amador; Jannet Rodríguez Valdés (Medisur)
Emergency care services have got an organizational tool of evident usefulness in the stratification of patients. This paper shows a stratification tool for diabetic patients with uncomplicated acute hyperglycemia in the Emergency Department. Group discussion, a process based on several guidelines or principles, was used in its design. The stratification tool classifies patients into one of four groups distinguishable from each other, which contribute to performance of different procedures on patients. It is based on the analysis of clinical information complemented with blood glucose readings, specifically for decision making; each group has a defined context, actions to take and pillars of therapeutic management, primarily focusing on insulin therapy. The tool is accompanied by a flow chart for management of diabetic patients with uncomplicated acute hyperglycemia in the yellow zone.